Program Pelatihan Empati Sebagai Strategi Mengurangi Perilaku Bullying pada Remaja - Aini, Kurrota; Rini, Hapsari Puspita (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to analyze the effectiveness of various empathy training programs, including Role-Playing, Effective Communication Training, Mindfulness-Based Interventions (MBIs), Peer Mediation Programs, Emotional Literacy Training, and Anti-Bullying Training Programs, in reducing bullying behavior among adolescents. Through a literature review approach, the study examines the impact and implementation of each program in developing empathy and social skills. The findings indicate that these programs can significantly reduce bullying incidents, although each program has its limitations, such as reliance on active student participation and resource constraints. This study emphasizes the importance of continuous training and school support for effective implementation. This research provides new insights for educators, practitioners, and policymakers in designing effective strategies to reduce bullying behavior and promote the development of empathy among adolescents